قراءة في النصوص القانونية المتعلقة بحق المستهلك في الإعلام والعدول عن العقد الإلكتروني في التشريعيين الجزائري والتونسي - دريس, فتحي كمال (جامعة الوادي - university of Eloued, 2017)
أمام إتساع نطاق التجارة الإلكترونية، سارعت بعض الدول إلى تقنينها لعدة أسباب، من بينها حماية المستهلك الذي يسعى إلى إقتناء السلع والخدمات بالوسائل الإلكترونية، هذه الأخيرة التي لا تخلوا من المخاطر، حيث يمثل فيها المستهلك الحلقة الأضعف، مما يفقد توازن المراكز القانونية بينه وبين العون الإقتصادي. لذلك حاولت مختلف التشريعات كفالة حقوق المستهلك في مثل هذه العقود، وارتأينا حصر الدراسة في حقين مرتبطين بمرحلة ما قبل التعاقد والمتمثلة في (حق الإعلام)، وما بعد التعاقد من خلال حق العدول، وذلك من خلال قراءة في النصوص القانونية ذات الصلة في التشريعين الجزائري والتونسي، إنطلاقا من الإشكالية الرئيسة التي يثيرها موضوع المداخلة وهي: ما مدى كفاية القواعد القانونية الواردة في التشريع الجزائري مقارنة بنظيره التونسي لكفالة حق المستهلك في الإعلام والعدول لدى التعاقد الإلكتروني؟ وللإجابة على الإشكالية السالفة الذكر إرتأينا تقسيم هذا المقال إلى محورين الأول يتعلق بحق المستهلك في الإعلام السابق لإبرام العقد الإلكتروني والثاني: حقه في العدول بعد إبرام العقد الإلكتروني. In front of the expansion of e-commerce, some countries were quick to ration it for several reasons, including consumer protection who seeks the acquisition of goods and services by electronic means, the latter of which is not without risks, where the consumer is the weakest link. Which loses the balance of legal centers between him and the economic aid. So various legislations tried to ensure the consumer’s rights in such contracts, and we decided to restrict the study in the two rights associated with the precontract phase as of "notification rights", and post- contract phase through the right to reverse, by reading the relevant Algerian and Tunisian legislatures legal texts, Proceeding from the main problem raised by the subject of intervention, namely: What is the adequacy of the legal rules contained in the Algerian legislation compared to Tunisian counterpart to ensure the consumer’s right to be notified, and the right to reverse, in terms of electronic contracting? To answer the above-mentioned problem, we decided to divide the article into two parts, first the consumer’s right to prenotification to conclude the electronic contract. Second, the right to reverse after the conclusion of the electronic contract.
مقال. المجلة الدولية للبحوث القانونية والسياسية . مج1. ع.1. جامعة الوادي
Keywords: العقد الإلكتروني، الإعلام، الإشهار الإلكتروني، سند المعاملة التجارية، العدول، آجاله، آثار العدول.; e-commerce, the consumer, the electronic contract, the right to reverse.